Novel synthesis of physovenine and physostigmine analogs. Issue 27 (6th July 2016) - Wang, C.H.; Alluri, S.; Nikogosyan, G.; DeCarlo, C.; Monteiro, C.; Mabagos, G.; Feng, H.H.; White, A.R.; Bartolini, M.; Andrisano, V.; Zhang, L.K.; Ganguly, A.K.
Graphical abstract: Highlights: Structurally diverse physovenine and physostigmine analogs were prepared. Radical reactions as the key step to construct the core structure. Establish the trend in SAR among physostigmine and physovenine analogs for activity against hAChE and hBuChE. Abstract: This Letter describes a versatile synthetic approach to prepare physovenine and physostigmine analogs. A series of analogs were synthesized and evaluated for cholinesterase inhibition activities, including human acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) from human serum.